Prove that:
Question:

Prove that: $\frac{(2 n+1) !}{n !}=2^{n}[1 \cdot 3 \cdot 5 \ldots(2 n-1)(2 n+1)]$

Solution:

$\mathrm{LHS}=\frac{(2 n+1) !}{n !}$

$=\frac{(2 n+1)(2 n)(2 n-1) \ldots .(4)(3)(2)(1)}{n !}$

$=\frac{[(1)(3)(5) \ldots \ldots \ldots .(2 n-1)(2 n+1)][(2)(4)(6) \ldots \ldots \ldots(2 n)]}{n !}$

$=\frac{2^{n}[(1)(3)(5) \ldots \ldots \ldots(2 n-1)(2 n+1)][(1)(2)(3) \ldots \ldots \ldots(n)]}{n !}$

$=\frac{2^{n}[(1)(3)(5) \ldots \ldots \ldots(2 n-1)(2 n+1)][n !]}{n !}$

$=2^{n}[(1)(3)(5) \ldots \ldots \ldots(2 n-1)(2 n+1)]=\mathrm{RHS}$

Hence, proved.

Administrator

Leave a comment

Please enter comment.
Please enter your name.